Field evidence of the interplay between rift and transform structures in the Krafla geothermal area, N-Iceland. (March 2021) - Liotta, Domenico; Brogi, Andrea; Árnadóttir, Sigurveig; Ágústsson, Kristján; Thorsteinsdóttir, Unnur
Highlights: Relation between geological structures and geothermal resources. Location of geothermal resources is controlled by fault interaction. Integration between fieldwork and geophysical data. Intersection of faults increases rock permeability. Abstract: The Krafla volcano-geothermal area is located in Northeast Iceland, within the active Northern Volcanic Zone sector of the axial rift and has experienced two eruptions in historical times. The Krafla system displays NNE-SSW oriented fissure swarm, a central volcano and associated geothermal manifestations (i.e. steam and gas emissions, hydrothermal alterations). However, during its exploration and exploitation, several geophysical indications have suggested the occurrence of WNW-ESE trending structures, i.e. near orthogonal with respect to the faults delimiting the axial rift. This paper describes the results of a structural survey carried out in a wide area in the NE-sector of Iceland along the Húsavík-Flatey shear zone and in the Krafla area, measuring fractures and alignments of geothermal manifestations and fissure swarms. The dataset highlights the occurrence of structures oriented in two main trends, i.e. NNW-SSE to NNE-SSW and WNW-ESE. At their intersection, geothermal manifestations and silica sinter deposits commonly occur. Both of these trends have been documented in the Krafla geothermal area and compared with borehole and geophysical data. Our conclusions support that the location of the high-temperature Krafla geothermal area is mainly controlled by the enhanced permeability at the intersection between structures of the axial rift zone and incipient transform faults crossing the Krafla area.